Notes on the diplomatic history of the Jewish question: with texts of protocols, treaty stipulations and other public acts and official documents - Wolf, Lucien (International legal material, 1919)
"The substance of this volume was read as a paper before the Jewish Historical Society of England on February 11, 1918. It has now been expanded and supplied with a full equipment of documents ... in the hopes that it may be useful ... to those of our communal organizations whose duty it will be to bring the still unsolved aspects of the Jewish Question before the coming Peace Conference". The book deals with the "Jewish question" in various European countries in the 19th-early 20th centuries. (From the Bibliography of the Vidal Sassoon International Center for the Study of Antisemitism)